A dark and dusty night: Razorback and the development of an environmentalist Australian Gothic cinema. Issue 1 (4th May 2021) - Rooks, Isaac
ABSTRACT: This article argues that Razorback 's self-aware play with cinematic Australian Gothic tropes infuses the aesthetic with an environmentalist sensibility that resonates in the Anthropocene. The limited scholarship addressing Razorback typically positions the film as a crude expression of the same anxieties found in New Wave Australian Gothic cinema. This interpretation misunderstands the role industrial maleficence plays in Razorback 's horror. In order to reassess Razorback, I situate this creature feature in the history of the Australian Gothic, a sensibility grounded in the country's settler colonial identity and focused on the unsettling qualities of the imposing natural landscape. Razorback draws on common tropes in Australian cinema – cultural anxiety around Americans, the tendency to idealize white rural life, and a fascination with the Outback – but it tweaks standard elements. Razorback offers a surreal take on the Outback, but it identifies its horror as stemming from human mismanagement and pollution of the natural world. The Outback becomes warped by the activities of the Baker Brothers, whose business breeds a monstrous manifestation of rapacious colonial capitalism and environmental degradation. This reassessment of an overlooked cult classic identifies Razorback as an important text to study in order to understand genre cinema's role in engaging environmental concerns.